Virtual Community as Platform Social Cohesion: A Case Study of Iraq - Shawkat, Aymen Riyadh (2010)
The Internet users are growing steadily in the field of social networks such as forums, blogs and groups. This life has created virtual communities which inherited all the advantages of the Internet on the one hand, and a structure of traditional communities on the other. This research was conducted to study the possibility to take advantage of the facilities offered by virtual communities, and used it to build social cohesion, through the investigation of the existence of factors affecting social cohesion within the virtual community. The hypothesis was tested on Iraq, a country that suffers from divisions and problems of political and social, through the selection of samples from the virtual community of Iraq and analyze data using content analysis technique; In addition, comparison of results derived from the virtual community with traditional society That showed great similarity, and the possibility of using ICT to build cohesion and community development, Which opens the door for more studies to organize the process and develop in the future.